ISLAMIC ECONOMIC CREATIVE SOLUTIONS FOR SMALL AND MEDIUM ENTERPRISES IN THE SHORT AND LONG TERM - Kadir, Syahruddin; Abdullah, M. Wahyuddin (Jurnal Iqtisaduna, 2019)
This study aims to find out the creative solutions of Islamic economics in overcoming the economic obstacles faced by SMEs both short and long term. This research is descriptive analysis with a qualitative approach from secondary data including and literature. The results of this study indicate that the right Islamic economic solution to addressing the economic barriers of SMEs is to provide Islamic finance, strengthen management, and use financial technology (Fintech) features and establish relationships with customers. This research has implications for improving and strengthening sharia-based SMEs.